Melodic Structure, Harmony, and Dissonance in Jaya Suprana’s Piano Work Dedemit - Kamaludin Galingging; Hendrik L Simanjuntak; Kartini R Manalu (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
This study examines a solo piano work by a second-generation Indonesian composer, following Amir Pasaribu and Mochtar Embut. Jaya Suprana is a pianist and composer, and is widely recognized as an Indonesian cultural figure. As the second generation in the context of Indonesian piano composers, Jaya Suprana has provided a milestone in expanding the concept of musical composition and introducing it to the international world. Through various musical performances, concerts, and recitals, Jaya Suprana's piano compositions have graced numerous venues both domestically and internationally. What's fascinating about Jaya Suprana's compositional concept is its difficult-to-interpret element of